2014
DOI: 10.1016/j.wace.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Future changes in extreme temperature events using the statistical downscaling model (SDSM) in the trans-boundary region of the Jhelum river basin

Abstract: a b s t r a c tIn the 21st century, climate change is considered to be one of the greatest environmental threats to the world, and the changes in climate extremes are estimated to have greater negative impacts on human society and the natural environment than the changes in mean climate. This study presents the projections of future changes in extreme temperature events under A2 and B2 SRES scenarios using the statistical downscaling model (SDSM) in the trans-boundary region of the Jhelum River basin. This are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 29 publications
(73 reference statements)
0
41
0
Order By: Relevance
“…In both seasons, the negative changes at Naran (ranging from 40%-73%) were greatly higher than Gari Habibullah, (ranging from 6% to 28%) under both A2 and B2. Mahmood and Babel [43] conducted a study about extreme temperature events in the Jhelum River basin under A2 and B2, and they found that the intensity of cold days and cold nights will increase in the future. The reduction in flow (as indicated by the results of this study) is likely to be the case due to more accumulation of snowfall that would result from the increased intensity of cold days and cold nights in winter (based on the projections of Mahmood and Babel that indicate that precipitation will increase in winter and decrease in spring) [1].…”
Section: Calibration and Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…In both seasons, the negative changes at Naran (ranging from 40%-73%) were greatly higher than Gari Habibullah, (ranging from 6% to 28%) under both A2 and B2. Mahmood and Babel [43] conducted a study about extreme temperature events in the Jhelum River basin under A2 and B2, and they found that the intensity of cold days and cold nights will increase in the future. The reduction in flow (as indicated by the results of this study) is likely to be the case due to more accumulation of snowfall that would result from the increased intensity of cold days and cold nights in winter (based on the projections of Mahmood and Babel that indicate that precipitation will increase in winter and decrease in spring) [1].…”
Section: Calibration and Validationmentioning
confidence: 99%
“…However, Q 95 was predicted to decrease by 18%-99% in the future in the basin. This might be due to the increase in the intensity of cold days and cold nights (mentioned by Mahmood and Babel [43]) which may cause precipitation as snow accumulation in winter (low flow season).…”
Section: Projected Changes In Mean Streamflowmentioning
confidence: 99%
See 1 more Smart Citation
“…resolutions (100-500 km) reduce their applicability where regional scales are concerned [5]. Regional/local scales require high resolution to adequately represent complex topographical features when the environmental and hydrological impacts of climate change are to be examined [5].…”
mentioning
confidence: 99%
“…Regional/local scales require high resolution to adequately represent complex topographical features when the environmental and hydrological impacts of climate change are to be examined [5]. In the last two decades, the statistical and dynamic downscaling models have been developed with the main aim of downscaling temporal and spatial outputs of GCMS at regional (50x50 km) and local (0-50 km) levels [6][7].…”
mentioning
confidence: 99%